The chironomids (Diptera, Chironomidae) described by Lundstr m (1915) from arctic Siberia, with a redescription of Derotanypus sibiricus (Kruglova & Chernovskii) - Sæther, Ole A. (Zootaxa, 2004)
The chironomid material described by Lundstr m (1915) from the Russian polar expedition in the years 1900 1903 is analysed. Derotanypus limbatus (Lundstr m, 1915) (as Ablabesmyia) is a senior synonym of Ablabesmyia quadrinotata Lundstr m, 1915; Orthocladius pubitarsis sensu Lundstr m, not Zetterstedt, 1838, is identical to Psectrocladius (Psectrocladius) sokolovae Zelentsov & Makarchenko, 1988; Orthocladius cinereipennis sensu Lundstr m, 1915, is a junior synonym of Heterotrissocladius subpilosus (Kieffer 1911); Orthocladius alpicola sensu Lundstr m, not Zetterstedt, 1850, is identical to Acricotopus lucens Zetterstedt, 1850; Orthocladius marginatus Lundstr m, 1915 a junior synonym of O. (Pogonocladius) consobrinus (Holmgren, 1869); Orthocladius (Orthocladius) nitidoscutellatus Lundstr m, 1915 a senior synonym of O. trigonolabis Edwards, 1924; Chaetocladius binotatus (Lundstr m, 1915) comb. n. probably a senior synonym of C. validus Brundin, 1956; Paralimnophyes trilineatus (Lundstr m, 1915) comb. n. a senior synonym of P. arcticus Brundin, 1956; Camptocladius incertus Lundstr m, 1915 a junior synonym of Chaetocladius perennis (Meigen, 1830); Chironomus lundstroemi sp. n. (= C. staegeri sensu Lundstr m, not Lundbeck, 1898), is described as male and female; Chironomus niveipennis sensu Lundstr m, not Fabricius, 1805, is identical to Chironomus trabicola Shobanov, W lker & Kiknadze, 2002. The following validly named and recognisable species are redescribed: Derotanypus limbatus (Lundstr m) (male and female); D. sibiricus (Kruglova & Chernovskii) (male and female); Diamesa chorea sensu Lundstr m, not Lundbeck, 1898, (female); Orthocladius pallidicornis Lundstr m, 1915 (male and female); Chaetocladius binotatus (Lundstr m) (male hypopygium); Chaetocladius perennis (Meigen, 1830) (male); Paralimnophyes trilineatus (Lundstr m) (male and female); Smittia brevipennis (Boheman, 1856) (female); C. flavoviridis Lundstr m, 1915 (female); C. trabicola (additions to male, female).